Teacher’s Roal to Increase Student Motivation in Ful DaySchooll System at Al Azhar Shiva Bodhi Solo High School (SMP Al-azhar Syifa Budi) - Abdullah Marhaban; Retno Wulandari (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2021)
Complete learning is a learning process that is carried out in a systematic and structured manner, aims to adapt learning to large group students (classical), help overcome differences in students and is useful for creating learning speeds (rate of program). Thorough learning that is carried out in the classroom is to help each student to complete their learning in the classroom. One of the factors that causes students to have difficulty completing class learning is the different abilities of students. So it is hoped that every teacher can adjust himself to each student, in order to make it easier for students to complete learning in the classroom. This type of research is descriptive qualitative research. This research was conducted at SMP Al-Azhar Syifa Budi Solo. Data were collected using (1) Observation Method (2) Interview method and (3) Documentation method. While the data analysis uses the Miles and Huberman model, with steps (1) data reduction (2) data presentation (3) conclusion and data validity. Based on the results of the research discussed by the researcher, it shows that the factors that influence student learning motivation (1) Lack of awareness and enthusiasm of each student (2) The abilities of each child are different. The efforts and roles made by the teacher in increasing student learning motivation (1) Accompanying the learning carried out in the classroom (2) Providing rewards as an additional value (3) Providing learning targets to students as an effort for students to be able to spur learning.